The Influence of Motivation, Competency, and Work Environment to The Work Achievement The Officer of The Hasanuddin University - Kustiany Kustiany (International Journal of Management Progress, 2019)
The role of quality human resources is very important to direct and formulate policies needed by organizations/agencies. The purpose of this study was to determine the Effect of Motivation, Competence and Work Environment on Employee Job Performance at the Head Office of Hasanuddin University. The method in collecting data in this study is a questionnaire, observation (observation), interviews and documentation. The method of data analysis uses inferential statistical methods namely by using multiple linear regression statistical methods to measure the Effect of Motivation, Competence and Work Environment on Employee Job Performance at the Head Office of Hasanuddin University. Based on the F test the independent variables (motivation, competence and work environment) together have a positive and significant effect on the dependent variable (job performance). Through testing the correlation coefficient (R) obtained that the correlation level of the relationship between Motivation, Competence and Work Environment Against Employee Job Performance is a high relationship that is 67.2%, while the remaining 32.8% is influenced by other factors. And motivation is the most dominant factor affecting the Job Performance of Hasanuddin University Headquarters.